The Socio-Economic Impact of Women Farmer’s Interest Group of Lac Growers - Singh, Atul; Singh, Kundan; Singh, Mukesh; Singh, Anjani Kumar; Bagri, Rajvendra (Indian Journal of Extension Education, 2018)
The present study was conducted on women farmer’s interest group of Tikariya village district Katni (MP) for the lac cultivation and their impact on socioeconomic condition of the women lac growers. The result revealed that the lac production increase the annual income of almost all the Lac growers has increased after adopting Lac production. Before the adoption of Lac production, the Lac grower’s annual household income varied from ` 28,000 to ` 65,000. The contribution of Lac grower in the annual household was varied from 18.46 to 37.14 per cent and average annual household was 31.41 per cent, before the adoption of Lac production. After the adoption of Lac production, the Contribution of Lac growers in the annual household income varied from ` 75,000 to ` 1, 23,000. The contribution of Lac growers, in the annual household is varied from 40.64 to 60.29 per cent. The increase in annual income household income varied from 47.15 per cent to 63.15 per cent and average annual household income 54.81 per cent. The increase in contribution of annual household income varied from 65.51 to 82.41 per cent. Subsequent to the acceptance of lac production, there was enormous increase in the annual household income and empowerment has lead to a change in their household and socio economic status of the Lac growers.
Keywords: Lac production; farmer interest group; NTFP